Overexpression of NtCET4 gene in tobacco promoted vegetative bud activity and delayed flowering - LONG Junlan; LUO Rui; LUO Xu; ZHANG Lan (Xibei zhiwu xuebao)
[Objective] The effect of NtCET4 gene overexpression in regulating tobacco flowering time was analyzed by constructing NtCET4 overexpression plants, and the feasibility of increasing the number of effective leaves of tobacco to improve tobacco yield based on NtCET4 manipulation was discussed. [Methods] Overexpression vector of NtCET4 was constructed. Transgenic individuals were obtained through the Agrobacterium-mediated leaf disc transformation. The transgenic plants were identified by PCR and GUS staining. The overexpressed lines were selected from transgenic lines based on qRT-PCR. The overexpressed plants were transplanted into fields to observe flowering time and leaf numbers. qRTPCR was used to identify relative expressions of NtCET4 before and after flowering. [Results] During the seedling stage, four transgenic lines showed significant increase in NtCET4 expression. These four transgenic lines with NtCET4 overexpression showed delaying flowering (about 14 days). Longer period of vegetative bud activity resulted in more valid leaves in the transgenic plants. NtCET4 expression in transgenic plants was increased from seedling to mature, and higher expression was detected before flowering relative to after flowering. [Conclusion] Overexpression of NtCET4 promotes the vegetative bud activity, delays flowering, and increases the number of valid leaves in tobacco.